Graphene Nanoribbon Hybridization of Zeolitic Imidazolate Framework Membranes for Intrinsic Molecular Separation. (26th October 2022) - Choi, Eunji; Choi, Ji Il; Kim, Yong‐Jae; Kim, Yeong Jae; Eum, Kiwon; Choi, Yunkyu; Kwon, Ohchan; Kim, Minsu; Choi, Wooyoung; Ji, Hyungjoon; Jang, Seung Soon; Kim, Dae Woo
Abstract: Zeolitic imidazolate frameworks (ZIFs) are promising for gas separation membrane, but their molecular cut‐off differs from that expected from its intrinsic aperture structure because of their flexibility. Herein, we introduced graphene nanoribbons (GNRs) to rigidify the ZIF framework. Because the sp 2 edge of the GNRs induces strong anchoring effects, the modified layer can be rigidified. Particularly, when the GNRs were embedded and distributed in the ZIF‐8 layer, an intrinsic aperture size of 3.4 Å was observed, resulting in high H2 /CO2 separation (H2 permeance: 5.2×10 −6  mol/m 2  Pa s, ideal selectivity: 142). The performance surpasses the upper bound of polycrystalline MOF membrane performance. In addition, the membrane can be applied to blue H2 production, as demonstrated with a simulated steam reformed gas containing H2 /CO2 /CH4 . The separation performance was retained in the presence of water. The fundamentals of the molecular transport through the rigid ZIF‐8 framework were revealed using molecular dynamics simulations. Abstract : The intrinsic aperture size of the zeolitic imidazolate framework (ZIF) is realized by embedding graphene nanoribbons into the crystal. Particularly, an intrinsic aperture size of 3.4 Å is observed for the ZIF‐8, resulting in sharp H2 /CO2 separation. The atomistic molecular transport mechanism is investigated with molecular dynamics simulation.